Graphics of maritime ships and boats demonstrating the relationship between Omani and Malaysian Malays. - Ahmad H.Osman, Rahmah; Alaa Eldin Allam, Amirah Hannan (2021)
Graphics of maritime ships and boats demonstrating the relationship between Omani and Malaysian Malays.